2017
DOI: 10.1080/10439463.2017.1311894
|View full text |Cite
|
Sign up to set email alerts
|

The virtues of strangers? Policing gender violence in Pacific Island countries

Abstract: This article considers the gap between reformist policy and practice in the policing of gender violence in Pacific Island Countries (PICs) with a key focus on Solomon Islands, Fiji and Kiribati. In doing so, we critically engage with two pervasive arguments in policing scholarship: (1) arguments regarding the value of hybridity and regulatory pluralism in PICs; and (2) the dominant critique of 'policing by strangers'. We outline and acknowledge the compelling logics of these arguments but we contend that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…In Kiribati, a program delivered in cooperation with cultural and religious authorities but based on RoL principles directly addressed police as perpetrators. For example, the slogans 'culture is no excuse for abuse' and 'religion is no excuse for abuse' were explicitly deployed to promote and reinforce the RoL in the face of competing customary or religious authority and change how these factors are viewed in normalising violence against women (Bull, George and Curth-Bibb 2019). This demonstrates that police authorities can also work with culture and faith to enhance their own capacity and responsiveness to gender violence when cases are brought to their attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Kiribati, a program delivered in cooperation with cultural and religious authorities but based on RoL principles directly addressed police as perpetrators. For example, the slogans 'culture is no excuse for abuse' and 'religion is no excuse for abuse' were explicitly deployed to promote and reinforce the RoL in the face of competing customary or religious authority and change how these factors are viewed in normalising violence against women (Bull, George and Curth-Bibb 2019). This demonstrates that police authorities can also work with culture and faith to enhance their own capacity and responsiveness to gender violence when cases are brought to their attention.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted in Samoa, Solomon Islands, Kiribati, Fiji, Vanuatu, Tonga and New Caledonia suggested that 40-70 per cent of women experience violence at the hands of intimate partners and family during their lifetimes (Fiji Women's Crisis Centre 2013; Ma'a Faffine mo e Famili 2012; Ride and Soaki 2019;Salomon and Hamelin 2010; Secretariat of the Pacific Community [SPC] 2006[SPC] , 2009a[SPC] , 2009bSPC and United Nations Population Fund 2001;Vanuatu Women's Centre [VWC] and Vanuatu Statistics Office 2011). Years of reform addressing state and community responses to this issue have made little difference to prevalence rates (Bull, George and Curth-Bibb 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There also appears to be a degree of under-reporting of some offence types, such as domestic violence (DV), drawing attention to the potential negative side of strong social bonding capital, which is often overlooked in social disorganisation theorists' accounts of crime (Scott & Hogg, 2015;. This raises questions about the possible value of overlaying a 'stranger policing' model to ensure access to justice for all victims, especially women (Bull et al, 2019). We conclude that policing in the TSR may present lessons for approaches elsewhere in remote Indigenous Australia, potentially informing efforts to de-colonise criminal justice.…”
Section: Introductionmentioning
confidence: 99%
“…Why Schutz and not others who use the stranger to understand the migrant (Best, 2019; Kennedy, 2018; Marotta, 2017; Rumford, 2013)? The importance of Schutz’s phenomenology of the stranger, unlike others, speaks directly to the nature of experience and its relation to knowledge construction and since its publication in 1944, Schutz’s essay on the stranger (1976b) has been cited over 2000 times (Google Scholar) and continues to be the point of reference in many contemporary studies on migration (Bull, George, & Curth-Bibb, 2019; Del Re, 2018; Fletcher & Swian, 2016; Horvat & Pušnik, 2019; Ju & Sandel, 2019; Sealy, 2018; Täubig, 2019). Hence, it is a pivotal text in our understanding of what constitutes the migrant experience and anything that comes after it is an implicit or explicit conversation with Schutz.…”
Section: Introductionmentioning
confidence: 99%